Forecasting Weekly Stock Price of PT. Aneka Tambang Tbk (ANTM) Using ARIMA Box-Jenkins Method - Wardhani, Andreanne Intan Sulistyo; Yudhanegara, Mokhammad Ridwan (Journal of Actuarial, Finance, and Risk Management, 2024)
Stock price movements in the dynamic economic world require investors and companies to be able to predict future price changes. One method that can be used to predict is Autoregressive Integrated Moving Average (ARIMA). The application of the ARIMA method to forecasting the share price of PT Aneka Tambang Tbk (ANTM) for 4 weeks produces equation   obtained from ARIMA (3,1,0) as the best model.